Analisis Pendidikan di India dan Perbandingannya dengan Pendidikan Indonesia - Thifa Ramadhani; Mislaini Mislaini; Liola Sinta (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2025)
This study aims to see and find out how education in India and its comparison with Indonesian education which includes the education system in India, character and physical education in India and Indonesia, coding learning and its comparison. This comparison provides insight for the improvement of the education system in India and in Indonesia. Basic Education Institutions are responsible for developing and implementing national character education in order to advance the nation's civilization, and produce quality human beings in all dimensions of their personality. Although in general, the educational curriculum in each country has similarities, but specifically each country has a unique difference between the education of one country and another, as well as the comparison of Indonesian and Indian education. The research method used is a qualitative descriptive method. Data collection techniques with literature studies.